STRATEGI PENGEMBANGAN UMKM BERBASIS DIGITAL DI KABUPATEN BANGGAI DALAM MENINGKATKAN DAYA SAING - Vivian Nova; Rifqah Ramdhana Jufri; Andi Muhammad Lukman; Amal Nur; Muhtar Muhtar (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
The rapid development of digital technology in recent years has created significant opportunities for Micro, Small, and Medium Enterprises (MSMEs) to improve operational efficiency, expand market reach, and strengthen competitiveness amid increasingly dynamic and competitive market conditions. Banggai Regency, as one of the regions experiencing rapid MSME growth, has also felt the impact of these changes. However, this progress is accompanied by various challenges, particularly the low level of digital literacy, limited access to capital, and the ability of business actors to adapt to new technologies. This study aims to analyze relevant and effective digital-based MSME development strategies to enhance the competitiveness of business actors in Banggai Regency. A descriptive qualitative approach was employed, with data collected through in-depth interviews with MSME actors, officials from the Office of Cooperatives and MSMEs, and business facilitators within the region. This method was chosen to obtain a comprehensive understanding of field conditions and the actual needs of MSMEs in their digital transformation process. The findings indicate that MSME strengthening strategies must focus on comprehensive digital transformation, including training on e-commerce platforms, optimization of social media for marketing, enhancement of digital branding, and the utilization of digital financial services such as e-wallets and fintech lending. Furthermore, collaboration among local governments, MSME communities, financial institutions, and private stakeholders plays a crucial role in building a sustainable digital ecosystem. Based on these findings, this study recommends the development of an integrated digital ecosystem in Banggai Regency, the establishment of local business incubators to provide continuous assistance to business actors, and the acceleration of technology-based access to capital. These efforts are expected to strengthen the adaptive capacity of MSMEs and improve their competitiveness in the digital economy era.